2005
DOI: 10.1017/s181638310018124x
|View full text |Cite
|
Sign up to set email alerts
|

Study on customary international humanitarian law: A contribution to the understanding and respect for the rule of law in armed conflict

Abstract: This article explains the rationale behind a study on customary international humanitarian law recently undertaken by the ICRC at the request of the International Conference of the Red Cross and Red Crescent. It describes the methodology used and how the study was organized and summarizes some major findings. It does not, however, purport to provide a complete overview or analysis of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…As mentioned earlier in this article, laws adopted by national parliaments are among acts that reveal state practice (Henckaerst 2005). National forestry laws of Central African states equally reveal SFM practices by each member.…”
Section: Domestic Sustainable Forest Management Lawsmentioning
confidence: 80%
“…As mentioned earlier in this article, laws adopted by national parliaments are among acts that reveal state practice (Henckaerst 2005). National forestry laws of Central African states equally reveal SFM practices by each member.…”
Section: Domestic Sustainable Forest Management Lawsmentioning
confidence: 80%
“…NIACs, in sufficient detail, the ICRC undertook a study of the customary international law applicable to these conflicts in 2005. 76 The study found that the vast majority of customary norms apply equally in both types of conflicts, thereby extending the rules applicable in IACs to NIACs. 77 Although the study is regarded as a valuable contribution, it is not above criticism.…”
Section: Possible Solutionsmentioning
confidence: 83%
“…Despite the above criticism, it remains true that in most of the decisions made by the European Court of Human Rights [108] illustrate that the overlaps in IHRL and IHL are likely to have influenced the ECHtR [42,109]. That influence has led to courts referring to IHRL as the preferred source of law when interpreting the state's obligations in situations of armed conflict.…”
Section: "The Court Observes That the Protection Of The Internationalmentioning
confidence: 99%